1999
DOI: 10.1111/j.1540-8159.1999.tb00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Time to First Shock in Implantable Cardioverter Defibrillator (ICD) Patients with Chagas Cardiomyopathy

Abstract: The incidence of appropriate ICD shocks within the first 6 months postimplantation was significantly higher in ChC patients than in CAD patients. ChC patients were younger and more often women than CAD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 11 publications
4
23
0
Order By: Relevance
“…The same group [61] expanded their findings when reported the results of ICD therapy in 20 patients with Chagas' disease with malignant ventricular arrhythmias in comparison to 35 patients with ischemic cardiomyopathy. No patient was treated with anti-arrhythmic drug after implantation.…”
Section: Secondary Prevention Of Sudden Cardiac Deathmentioning
confidence: 84%
“…The same group [61] expanded their findings when reported the results of ICD therapy in 20 patients with Chagas' disease with malignant ventricular arrhythmias in comparison to 35 patients with ischemic cardiomyopathy. No patient was treated with anti-arrhythmic drug after implantation.…”
Section: Secondary Prevention Of Sudden Cardiac Deathmentioning
confidence: 84%
“…There are only few non-randomized studies demonstrating the efficacy of ICD in CCM. Nevertheless, we believe ICDs should be strongly considered for this population, since the occurrence of fatal arrhythmias might be higher in these patients than in others who are candidates for such devices [4]. CardinalliNeto et al [3], suggested that chagasic patients undergoing transvenous ICD implantation after recovered cardiac arrest have peculiar arrhythmogenic profile characterized by high 89 Letters to the Editor frequency of ventricular fibrillation, no left ventricular systolic dysfunction and short period of time for first shock.…”
Section: Discussionmentioning
confidence: 98%
“…All of these studies investigated patients for whom ICD was indicated for the prevention of arrhythmias secondary to ChD. Studies by Muratore et al (50), (51) and Fonseca et al (53) found no difference between the populations with and without Chagas disease in the numbers of arrhythmia episodes, shocks, and deaths. In contrast, the studies by Martinelli-Filho et al (44) , Rabinovich et al (51) , Moreira (49) , Cardinalli-Neto et al (54) , Cardinalli-Neto et al (55) , Barbosa et al (52) and the ICD registry for patients with Chagas disease in Latin America, published in 2009 (56) , found differences between the chagasic and non-chagasic populations.…”
Section: Implantable Cardioverter Defi Brillatormentioning
confidence: 99%
“…Studies of ICD implantation in patients with ChD have aimed to evaluate its effi cacy and safety and to identify predictors of appropriate therapy (47), (48) . In addition, several studies have compared the results of ICD implantation in ChD patients with the results of ICD implantation in the non-chagasic population to identify similarities and differences between these populations (44), (49)(50)(51)(52) . All of these studies investigated patients for whom ICD was indicated for the prevention of arrhythmias secondary to ChD.…”
Section: Implantable Cardioverter Defi Brillatormentioning
confidence: 99%